Zasebnost in dostojanstvo pacienta - Marinič, Milena (Obzornik zdravstvene nege, 2012)
The article discusses the global issue of current protection of patient privacy and confidentiality. According to available data on sanctions against offenders who breached patient data privacy, the patients' dignity and privacyare not sufficiently protected. The aim of the article is to present some misuses or disclosures of patient personal health information and the Slovene legislation which is too broad to safeguard the use, disclosure and storage of personal health information. The Act on Patient's Rights and the Personal Data Protection Act do not include explicit enough regulations and clear guidelines for sanctions against offenders in all cases of personal datamisuse. Presented in the article is the analysis of non-personal sources, such as legislative acts and judicial decisions of the Slovenian Court and theEuropean Court of Human Rights in relation to privacy and personal health information violation. The use and disclosure of individually identifiable health information may affect the patient's integrity and entail sanctions for the health providers. In conclusion, the fact that domestic legislation allows for too broad interpretation to fully protect the patient health data privacy is accentuated.
Keywords: dignity; dostojanstvo; health information; pacienti; privacy; varstvo podatkov; zasebnost; zdravstveni podatki